2022
DOI: 10.3389/fimmu.2022.939394
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchy of selection pressures determines the organization of the T cell receptor repertoire

Abstract: We systematically examine the receptor repertoire in T cell subsets in young, adult, and LCMV-infected mice. Somatic recombination generates diversity, resulting in the limited overlap between nucleotide sequences of different repertoires even within the same individual. However, statistical features of the repertoire, quantified by the V gene and CDR3 k-mer frequency distributions, are highly conserved. A hierarchy of immunological processes drives the evolution of this structure. Intra-thymic divergence of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…We sequenced the TCR repertoire of naive, central memory and effector memory CD4+ and CD8+ T cells from the spleen and bone marrow of three to four C57BL/6 mice at 8 - and 40-days post LCMV infection (summarized in Figure 1A ). The library preparation incorporates molecular identifiers (UMI) for each cDNA molecule, which allows subsequent correction for PCR bias and sequencing error, allowing a robust and quantitative annotation of each sequence in terms of CDR3 sequence and frequency ( 22 , 23 , 30 ); About ~1.89 x10 6 annotated CDR3 nucleotide beta chains were obtained, including a varied number of sequences between compartments, tissues, and infection status ( SI Table 1 ), which positively correlates with the number of sorted cells ( SI Figure 1C ). Our analysis focuses mainly on the amino acid sequence of the TCR beta complementarity determining region 3 (CDR3βAA), which is the most diverse region of the TCR molecule and is associated with antigen epitope recognition ( 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We sequenced the TCR repertoire of naive, central memory and effector memory CD4+ and CD8+ T cells from the spleen and bone marrow of three to four C57BL/6 mice at 8 - and 40-days post LCMV infection (summarized in Figure 1A ). The library preparation incorporates molecular identifiers (UMI) for each cDNA molecule, which allows subsequent correction for PCR bias and sequencing error, allowing a robust and quantitative annotation of each sequence in terms of CDR3 sequence and frequency ( 22 , 23 , 30 ); About ~1.89 x10 6 annotated CDR3 nucleotide beta chains were obtained, including a varied number of sequences between compartments, tissues, and infection status ( SI Table 1 ), which positively correlates with the number of sorted cells ( SI Figure 1C ). Our analysis focuses mainly on the amino acid sequence of the TCR beta complementarity determining region 3 (CDR3βAA), which is the most diverse region of the TCR molecule and is associated with antigen epitope recognition ( 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We were interested in the impact of infection on driving convergence (increased sharing) versus divergence (decreased TCR sharing) between repertoires. In order to quantify repertoire overlap, while incorporating TCR abundance, we used the pairwise cosine distance between the abundance vectors for each repertoire (see M&M in ( 23 )) to create a matrix of similarities between all pairs of repertoires. We have previously shown that this measure is highly correlated to the Morisita overlap index.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Technically, this implies a high purity of the samples, which is essential to characterise TCR repertoires. Biologically, it means not only that the TCR repertoire of CD4 and CD8 cells are different (Bergot et al, 2015;Camaglia et al, 2023;Mark et al, 2022), but that the CD4/CD8 lineage choice of T cells is completely TCR-driven, and that this choice is made consistently within and between mice. In other words, it shows that CD4/CD8 fate choice is largely deterministic, although it is based on the affinity of the TCR for a large variety of self-peptide/MHC complexes.…”
Section: The Tcr Repertoire Is Reproducible and The Results Of Determ...mentioning
confidence: 99%